Multiple hemangiomas and hemangiomatosis: risk factors and outcome over an eight year period - Schupp, Christine; Holland-Cunz, Stefan; Schenk, Jens-Peter; Weisser, H.; Grimm, Dirk; Günther, Patrick (European journal of pediatric surgery, 2010)
Hemangiomas are the most common tumors of infancy. Multiple cutaneous hemangiomas may be associated with the presence of hemangiomas in inner organs. However, there is little data on the risk factors for organ involvement and the outcome of a large sample of patients.